Effect of different drying methods on the bioactive, microstructural, and in-vitro bioaccessibility of bioactive compounds of the pomegranate arils - Ozay-Arancioglu, Irem; Bekiroglu, Hatice; Karadag, Ayse; Saroglu, Oznur; Tekin-Cakmak, Zeynep Hazal; Karasu, Salih (SOC BRASILEIRA CIENCIA TECNOLOGIA ALIMENTOS, 2022)
This study aimed to investigate the effect of different drying methods on the drying kinetic, total bioactive content, in-vitro bioaccessibility of bioactive compounds, and color and microstructural properties of pomegranate arils. Drying methods significantly affected all selected parameters of dried pomegranate arils (P<0.05). Freeze-drying (FD) showed higher bioactive compounds, lower shrinkage, and better color quality than those of other samples. Ultrasound-assisted vacuum drying (UAVD) showed lower drying times, lower shrinkage, and higher bioactive compounds than vacuum drying (VD) and hot air drying (HAD). The ABTS, CUPRAC, and DPPH results were 34.53-63.71 mu mol TE/g, 29.70-61.60 mu mol TE/g and 64.82-93.69% DPPH radical scavenging activity, respectively. Also, the highest values of antioxidant capacity for all methods were obtained from the samples dried with FD followed by UAVD, VD, and HAD. The recovery of TPC in dried and fresh samples changed from 2.58% (fresh pomegranate) to 10.32% (vacuum-dried pomegranate). The recovery of TPC for freeze-dried samples (2.62%) was closest to the fresh ones and VD showed the highest TPC recovery. This study suggested that UAVD and VD should be used as alternative methods to HAD due to higher bioactive compounds retention, better color and surface quality, and higher recovery of bioactive compounds.
Keywords: ultrasound-assisted vacuum drying; in-vitro bioaccessibility; pomegranate aril; vacuum drying; GASTROINTESTINAL DIGESTION; ANTIOXIDANT CAPACITY; CHEMICAL-COMPOSITION; PHENOLIC-COMPOUNDS; SENSORY QUALITY; HOT-AIR; VACUUM; KINETICS; FOOD; ANTHOCYANINS; Food Science & Technology